The Effect of Unfractionated vs. Low Molecular Weight Heparin on Tissue Factor Pathway Inhibitor Levels in Hospital Inpatients - Brown, Jennifer R.; Kuter, David J. (Thrombosis and Haemostasis, 2001)
Although heparin is widely used as an antithrombotic agent, its multiple mechanisms of action are not fully defined. Recent work has suggested that tissue factor pathway inhibitor (TFPI) may contribute to the antithrombotic activity of heparin by inhibiting the extrinsic pathway of coagulation. We have investigated the effect of heparin on TFPI and have found that when unfractionated heparin is given by continuous intravenous infusion to hospitalized inpatients, TFPI levels increase 2.3-fold and remain high as long as heparin is continued, but return to baseline levels soon after the infusion is stopped. In contrast, therapeutic doses of the low molecular weight heparin, dalteparin, resulted in significantly less TFPI induction. Given the increasing number of studies establishing the clinical efficacy of low molecular weight heparins as antithrombotic agents, these results suggest that TFPI may not be a major contributor to the antithrombotic effect of heparin.
Keywords: Heparin; dalteparin; tissue factor pathway inhibitor; extrinsic pathway; low molecular weight heparin